ANALISIS KURIKULUM JURUSAN PENDIDIKAN SENI TEATER ETHIOPIA - Sinshaw, Girmaw Ashebir (FBS UNY, 2019)
Tujuan penulisan artikel ini adalah untuk menganalisis pendidikan seni teater Ethiopia sebagai bentuk seni kreatif. Di Ethiopia, seni teater baru terbentuk tahun 1978, yang hingga sekarang belum menunjukkan kemajuannya. Kurikulum pendidikan seni teater di Ethiopia belum terlihat baik, dalam arti masih terdapat kekurangan di sana sini, sehingga sampai sekarang masih perlu penyempurnaan. Pendidikan seni teater ditopang oleh jurusan seni yang lain di Universitas Addis Ababa. Hal ini menyebabkan aspek musik, tari, seni rupa, dan seni kriya ikut membentuk terbentuknya pendidikan seni teater. Sekarang, pendidikan seni teater disuntik dengan seni teater tradisional yang menyebabkan bentuknya menjadi seni kreatif namun tidak menunjukkan teater yang mapan. Setiap teater di Ethiopia memilih bahan baku untuk memakmurkan pendidikan seni teater yang sekarang sedang digarap dalam kurikulum pendidikan seni teater Ethiopia. Kata Kunci: teater, pendidikan seni, kurikulum, senikreatif, Ethiopia CURRICULUM ANALYSIS OF THETHEATRE ARTS EDUCATION DEPARTMENT IN ETHIOPIA Abstract The purpose of this article is to analyze the theatrearts education in Ethiopia as a form of creative arts. In Ethiopia, the new theatrearts were formed in 1978, which until now has not shown significant progress. There are still shortages here and there in the curriculum for theatre arts education in Ethiopia, so that it still needs improvement. Theatre education is supported by other art majors at Addis Ababa University. This has caused aspects of music, dance, visual arts, and art to form the formation of theatrearts education. Now, the theatrearts education isinjected with traditional theatre arts, causing their form to become creative arts but not showing established theatre. Likewise, theatre arts in Ethiopia choose raw materials to prosper the theatrearts education which is now being worked on in the Ethiopian theatre arts education curriculum. Keywords: theatre, arts education, curriculum, creative arts, Ethiopia